NOVEL AUTOMATIC TEXT CLASSIFICATION TECHNIQUE USING NATURAL LANGUAGE PROCESSING (International Journal of Food and Nutritional Sciences, 2021)
In this informative age, many documents in different Indian Languages are available in digital forms. For easy retrieval of these digitized documents, these documents must be classified into a class according to its content. Text Classification is an area of Text Mining which helps to overcome this challenge. Text Classification is act of assigning classes to documents Text mining and natural language processing are fast growing areas of research, with numerous applications in business, science and creative industries. Automated text classification has been considered as a vital method to manage and process a vast amount of documents in digital forms that are widespread and continuously increasing. In general, text classification plays an important role in information extraction and summarization, text retrieval, and question answering. The demand of text classification is growing significantly in web searching, data mining, web ranking, recommendation systems and so many other fields of information and technology. To solve these issues, Novel automatic text classification technique using Natural Language Processing (NLP) is presented in this work. The performance of presented approach is evaluated in terms of accuracy and sensitivity. It will achieve better results compared to earlier approaches.